(untitled) (Journal of Information Technologies in Education (ITE), 2021)
Ensuring the quality of professional training of future math teachers by means of information and communication technologies involves the organization of professional training, which is based on the interrelated principles of state policy in education, the principles of organization of the pedagogical process, the principles of teaching (didactics). The article considers the professional functions, typical tasks and skills that must be possessed by future math teachers, specifies the main components of the professional activity of the future math teacher with the use of ICT in continuing education. Continuing education is seen as a new integrative entity, which is characterized by dynamism, flexibility, continuity and is to merge the basic and further preparation of man for work and social activities in a single holistic educational process. The math teacher’s professional activity directly depends on the preparation of the future math teacher in the context of continuing education and provides targeted activities for students to acquire knowledge and master the skills and abilities that will be used to stimulate student personality. Speaking about the use of ICT in the professional activities of math teachers, we need to pay attention to improving the training of future math teachers, namely the diverse development of personality through ICT, which provides a high degree of work activity, mobility and adaptability to rapidly changing working conditions. Changing the forms of teaching future math teachers is moving towards blended learning and involves the use of both traditional forms of higher mathematics (lectures, workshops, seminars, consultations, independent work, etc.) and innovative (interactive video lectures, distributed comp. computer-oriented practical works, webinars, mobile consultations, etc., which provide an opportunity to combine formal and non-formal learning). Thus, readiness for pedagogical activity is considered as result and purpose of professional training and professional competence is considered not only as result of professional training.